Mark's other gospel : rethinking Morton Smith's controversial discovery - Brown, Scott G. (Scott Gregory), 1966- (Studies in Christianity and Judaism ;, 2005)
Did the evangelist Mark write two versions of his gospel? According to a letter ascribed to Clement of Alexandria, Mark created a second, more spiritual edition of his gospel for theologically advanced Christians in Alexandria. Clement's letter contains two extracts from this lost gospel, including a remarkable account of the raising of Lazarus. While scholars have reacted to this longer Gospel of Mark in different ways, after forty-five years of cursory investigation, one of the few things on which most scholars agree is that the letter's own explanation of the origin and purpose of this longer gospel need not be taken seriously. 'Mark's Other Gospel' calls this pervasive bias into question. After thoroughly critiquing the five competing scholarly paradigms regarding the gospel's status, Scott G Brown demonstrates that the gospel excerpts not only sound like Mark, but also employ Mark's distinctive literary techniques, deepening this gospel's theology and elucidating puzzling aspects of its narrative.; This 'mystic gospel' would have served the interests of educated Alexandrian readers, who expected to discover essential truths of a philosophy beneath the literal level of revered texts.